Distal Ulna Hook Plate: Angular Stable Implant for Fixation of Distal Ulna - Nunez, Fiesky A., Jr.; Li, Zhongyu; Campbell, Douglas; Nunez, Fiesky A., Sr. (Journal of Wrist Surgery, 2013)
Distal ulna fractures, especially styloid injuries, classically have not been repaired, and only recently have these injuries been considered important. Certain fracture patterns of the distal ulna contribute to distal radioulnar joint (DRUJ) incongruity and potential instability. Appropriate fixation of the distal ulna is frequently difficult for several reasons: (1) high incidence of osteoporois in the affected patient population, (2) proximity of the injury to articular surfaces, and (3) lack of a proper implant to treat these injuries. The 2.0-mm locking compression distal ulna plate (LC-DUP) is an anatomically contoured implant with a low profile and fixed angle that provides proper stability to treat injuries of the distal ulna. The plate was designed for the treatment of distal ulna fractures, but its success has led to an extension of its indications to be used in treating symptomatic basistyloid ulnar nonunions and in ulnar shortening osteotomy for ulnocarpal abutment syndrome. The authors' description of the techniques used for each indication as well as their perspectives in the treatment of distal ulna injuries are described in detail in this report.
Keywords: distal ulna fracture; DUP; LC-DUP; distal ulna hook plate; ulnar styloid; ulnocarpal abutment syndrome; ulnar impaction syndrome; ulna nonunion; ulna fracture; ulnar shortening osteotomy